Oral Fluid Analysis for Drivers Under the Influence of Drugs - Akgür, Serap Annette; Dönmez, Tamer; Yemişçigil, Ali (The Bulletin of Legal Medicine, 2006)
The contribution of drugs to traffic accidents has been evaluated in a number of publications. In the last decade, several interesting development have occurred in the field of roadside testing for drugs. The need for a rapid, valid and suitable roadside test for the abused drugs focused the attention on alternative matrixes including oral fluid, urine and sweat, for detecting the drivers under the influence of drugs (DUID). European Union (EU)-project ROSITA (Road Side Testing Assessment) revealed that, a wide variety of illicit drugs can be found in different biological specimen of drivers where cannabis, opiates, amphetamine and its derivatives are those with the highest prevalence. Ege University and Head Council of Turkish Police coordinated and Cozart Bioscience Limited supported this project. The objectives of this project were to detect the usability and practicability of this test, besides revealing the possible problems during roadside drug testing encountered by the police. This study was performed on an experimental basis with voluntary participation of randomly selected drivers for the detection of abused drugs in street traffic, besides alcohol. They agreed to participate through informed consent. Oral fluid testing ( Cozart Rapiscan drug testing) for five panel drugs (Can-nabinoids, amphetamine, cocaine, opiates, benzodiazepines) was performed. 25 oral fluid samples were screened according to Cozart Bioscience instructions,. Confirmation was made by GC-MS. The oral fluid sample was positive for MDA at a concentration of 65 ng/mL and for MDMA at a concentration of 180 ng/mL. Key words: Driving under the influence of drugs (DUID), roadside drug testing, oral fluid